Preferences for European unemployment insurance: a question of economic ideology or EU support?. Issue 2 (1st February 2020) - Kuhn, Theresa; Nicoli, Francesco; Vandenbroucke, Frank
ABSTRACT: Against the backdrop of proposals to introduce a European unemployment insurance scheme, we study public support for such schemes by conducting a conjoint experiment on support for European unemployment insurance in 13 EU member states. We argue that European-level social policy initiatives and the underlying notions of solidarity cannot be reduced to a one-dimensional concept, but rather include various dimensions. Unemployment schemes vary in their generosity, the conditions for support, their impact on taxation, the extent to which they preclude permanent redistribution between countries, and the EU's role in their administration. Generosity, conditions and taxation are 'domestic' dimensions, since they mainly resonate with domestic policy debates; between-country redistribution and administration are 'cross-border' dimensions, referring to relationships between countries. We expect economic ideology to interact predominantly with domestic dimensions and EU support to interact predominantly with cross-border dimensions. Findings confirm these expectations, with the exception of between-country redistribution and country-level conditionality.